PHYTO-GEOGRAPHICAL ANALYSIS OF THE FLORA OF COASTAL ECOSYSTEMS OF THE LOWLAND DAGESTAN - Z. I. Soltanmuradova (Ûg Rossii: Èkologiâ, Razvitie, 2014)
The article presents phyto-geographical analysis of the flora of coastal ecosystems of the lowland Dagestan. Found 24 geographical elements. Provides quantitative and percentage of geo-types and geo-elements.